Synthetic materials in craniofacial regenerative medicine: A comprehensive overview - Yazdanian, Mohsen; Alam, Mostafa; Abbasi, Kamyar; Rahbar, Mahdi; Farjood, Amin; Tahmasebi, Elahe; Tebyaniyan, Hamid; Ranjbar, Reza; Hesam Arefi, Arian (Frontiers in Bioengineering and Biotechnology, 2022)
The state-of-the-art approach to regenerating different tissues and organs is tissue engineering which includes the three parts of stem cells (SCs), scaffolds, and growth factors. Cellular behaviors such as propagation, differentiation, and assembling the extracellular matrix (ECM) are influenced by the cell's microenvironment. Imitating the cell's natural environment, such as scaffolds, is vital to create appropriate tissue. Craniofacial tissue engineering refers to regenerating tissues found in the brain and the face parts such as bone, muscle, and artery. More biocompatible and biodegradable scaffolds are more commensurate with tissue remodeling and more appropriate for cell culture, signaling, and adhesion. Synthetic materials play significant roles and have become more prevalent in medical applications. They have also been used in different forms for producing a microenvironment as ECM for cells. Synthetic scaffolds may be comprised of polymers, bioceramics, or hybrids of natural/synthetic materials. Synthetic scaffolds have produced ECM-like materials that can properly mimic and regulate the tissue microenvironment's physical, mechanical, chemical, and biological properties, manage adherence of biomolecules and adjust the material's degradability. The present review article is focused on synthetic materials used in craniofacial tissue engineering in recent decades.